Synthesis of hierarchical MFI zeolites with a micro–macroporous core@mesoporous shell structure. Issue 6 (21st December 2018) - Zhang, Yunjuan; Han, Xinbao; Che, Shunai
Abstract : Core–shell structured ZSM-5 zeolites were synthesized by using a bifunctional surfactant containing alkene group in the hydrophobic tail. Abstract : Core–shell structured ZSM-5 zeolites (CSSZs) consisting of a micro–macroporous zeolite core and a mesoporous zeolite shell were synthesized by using a bifunctional surfactant containing an alkene group in the hydrophobic tail. The alkene tail and aluminum concentration are the key factors for the formation of the mesoporous shell in CSSZs.